PERSEPSI WISATAWAN TENTANG SAPTA PESONA PANTAI TIRAM KABUPATEN PADANG PARIAMAN - Putri, Mairihda; Yuliana, Yuliana; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
This study destination to determine the perception Tourist about Sapta Pesona Beach Tiram Padang Pariaman the views of 4 indicators are safe, order, clean and ramahtamah. This type of research is descriptive quantitative. The population of this study is that tourists are moderate and frequent visits to Coast Tiram, amounting to 280 people. Selection of the sample using incidental sampling technique (100 people). Collecting data using a questionnaire based on Likert Scale which has been tested for validity and reliability. Data were analyzed using the average formula ideal research (Mi), and standard deviation (Sdi). The results showed that in general the perception of tourists about the Sapta Pesona Beach Padang Pariaman Tiram are categories include good enough with a value score 95.03. Sapta pesona seen from the indicator with the value score 28.98, orderly with a value score 28.34. Clean with a value score 20.84. Ramah tamah with a value score 16.87. Keywords : Perception, Sapta Pesona, Tourist